How Do Banking Crises Affect Bilateral Exports? - Kiendrebeogo, Youssouf (IMF Working Papers; Working Paper ;, 2013)
This paper investigates whether banking crises are associated with declines in bilateral exports. We first develop a simple open economy model in which banking crises translate into negative liquidity shocks, leading to collapses in exports through supply-side and demand-side shocks. We then estimate a gravity model using a sample of developed and developing countries over the period 1988-2010. The results suggest that crisis-hit countries experience lower levels of bilateral exports, particularly in developing countries where supply-side shocks are found to be relatively more important than demand shocks. In developing countries, exports of manufactured goods are disproportionately hurt by banking crises and this negative effect is stronger in industries relying more on external finance. These findings are robust to correcting for potential endogeneity, to changes in the sample, and to alternative estimation methods.